Practice makes voters? Effects of student mock elections on turnout - Richard Öhrvall; Sven Oskarsson (Research Institute of Industrial Economics (IFN), 2018)
Student mock elections are carried out in schools around the world in an effort to increase political interest and efficacy among students. There is, however, a lack of research on whether mock elections in schools enhance voter turnout in real elections. In this paper, we examine whether the propensity to vote in Swedish elections is higher among young people who have previously experienced a student mock election. The analysis is based on unique administrative population-wide data on turnout in the Swedish 2010 parliamentary election and the 2009 European Parliament election. Our results show that having experienced a mock election as a student does not increase the likelihood of voting in subsequent real elections. This result holds when we study both shortand long-term effects, and when we divide our sample into different parts depending on their socio-economic status and study each part separately.
Keywords: D10; D72; I24; I28; 330; Political inequality; Student mock elections; Voter turnout; Education